Prognostic value of the Naples Prognostic Score in adult chronic obstructive pulmonary disease: NHANES 2005–2018 - Kang, Yue; Tan, Yingjian; Tie, Yongxin; Zhang, Yujing; Cui, Chenyu; Zhao, Yuanyuan (Frontiers in Nutrition, 2024)
Background Previous studies have demonstrated that the Naples Prognostic Score (NPS) provides strategic direction in the prognosis of malignant illness. Nevertheless, its relationship with chronic obstructive pulmonary disease (COPD) remains underexplored. Therefore, additional research specifically focusing on the relationship between the Naples Prognostic Score and COPD is necessary to determine its widespread applicability. Objectives The objective was to explore the relationship between the NPS and the susceptibility to developing COPD. Methods A total of 15,184 participants were included in our research, and statistical analyses were performed after weighting. We used weighted logistic regression to assess whether the NPS and COPD had a relationship, as well as its association with lung function. Subgroup analysis was used to detect the interaction. In addition, Kaplan–Meier survival curves were generated, and adjusted hazard ratios of different causes of death were calculated using Cox regression. Results Our investigation examined 15,184 participants’ data and then revealed a significant positive link between the NPS and COPD risk, while smoking has an interactive effect on it. A trend toward a decreasing prevalence of lung function indicators such as FEV1 [OR (95%CI), −339.70 (−456.53, −222.87)], FVC [OR (95%CI), −296.70 (−435.34, −158.06)], FEV1/FVC [OR (95%CI), −0.03 (−0.04, −0.02)], predicted FEV1 [OR (95%CI), −0.09 (−0.14, −0.04)], and predicted FVC [OR (95%CI), −0.08 (−0.15, −0.01)] was observed with increased NPS levels. Survival curves were drawn, and Cox regression analysis was conducted by dividing participants into group 0, group 1, and group 2 with NPS values of 0, 1–2, and 3–4, respectively. After assigning participants to groups 0, 1, and 2, with NPS values of 0, 1–2, and 3–4, respectively, the survival curves were created, and the Cox regression analysis was carried out. All-cause mortality [HR (95%CI), 1.68 (1.39–2.85)] and hypertension-related mortality [HR (95%CI), 67.64 (8.88–515.07)] of group 2 were significantly elevated. Conclusion The findings of this study suggested that the NPS serves as a robust prognostic indicator of COPD.